Socio-environmental dynamics along the historical silk road - Yang, Liang Emlyn; Bork, Hans-Rudolf; Fang, Xiuqi; Mischke, Steffen (Springer International Publishing, 2019)
This open access book discusses socio-environmental interactions in the middle to late Holocene, covering specific areas along the ancient Silk Road regions. Over twenty chapters provide insight into this topic from various disciplinary angles and perspectives, ranging from archaeology, paleoclimatology, antiquity, historical geography, agriculture, carving art and literacy. The Silk Road is a modern concept for an ancient network of trade routes that for centuries facilitated and intensified processes of cultural interaction and goods exchange between West China, Central Asia, the Middle East, and the Mediterranean. Coherent patterns and synchronous events in history suggest possible links between social upheaval, resource utilization and climate or environment forces along the Silk Road and in a broader area. Post-graduates in studying will benefit from this work, as well as it will stimulate young researchers to further explore the role played by the environment in long-term socio-cultural changes
Open Access